Afrasian Languages - Diakonoff, Igor' Michajlovič (1988)
Translated from the Russian by A.A. Korolev and V.Ya. Porkhomovsky. Revised Edition of Semito-Hamitic Languages, 1965, 28:480, die eine Übersetzung aus dem Russischen, 27 c 56a, bietet